2013
DOI: 10.1074/jbc.m113.471573
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin Bound to α2-Macroglobulin Reduces Ferroportin-1 Expression and Enhances Its Activity at Reducing Serum Iron Levels

Abstract: Background:Hepcidin is the hormone of iron metabolism that is bound by ␣ 2 -macroglobulin (␣ 2 M) and its activated counterpart (␣ 2 M-MA). Results: Serum iron is reduced to a greater extent in mice treated with ␣ 2 M⅐hepcidin or ␣ 2 M-MA⅐hepcidin relative to unbound hepcidin. Conclusion: ␣ 2 M retards hepcidin excretion by the kidney, increasing its efficacy. Significance: These results are important for understanding hepcidin transport and detection in blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 62 publications
(112 reference statements)
1
17
1
Order By: Relevance
“…However, because samples were only at room temperature for approximately 8 h during sample set preparation, the contribution to isoform formation was likely negligible. Furthermore, it is unclear whether measurement procedures measure free hepcidin or hepcidin bound to ␣2-macroglobulin, which might contribute to heterogeneity to an unknown extent (23)(24)(25). Regardless of the cause of heterogeneity, it can only be reduced by assay modification, not by harmonization.…”
Section: Current Equivalence Between Measurement Proceduresmentioning
confidence: 99%
“…However, because samples were only at room temperature for approximately 8 h during sample set preparation, the contribution to isoform formation was likely negligible. Furthermore, it is unclear whether measurement procedures measure free hepcidin or hepcidin bound to ␣2-macroglobulin, which might contribute to heterogeneity to an unknown extent (23)(24)(25). Regardless of the cause of heterogeneity, it can only be reduced by assay modification, not by harmonization.…”
Section: Current Equivalence Between Measurement Proceduresmentioning
confidence: 99%
“…10,11 The (unbound) hepcidin is freely filtered across the glomerular membrane, which was shown in two murine studies in which radiolabeled human hepcidin (hhep) was administered intraperitoneally and intravenously and measured in urine. 12,13 Indeed, plasma hepcidin levels were increased compared with baseline after CABG, which may have contributed to the elevated urinary hepcidin levels observed in these patients. However, plasma hepcidin levels were not associated with development of AKI.…”
mentioning
confidence: 96%
“…The recent study by Huang et al showed that serum iron levels are reduced to a significantly greater extent in mice treated with α 2 -macroglobulin-hepcidin complex than in those treated with unbound hepcidin. The researchers suggested that this binding delays hepcidin excretion by the kidney and increases its circulatory half-life and efficacy compared to free hepcidin (unbound 125 I-hepcidin was significantly increased in the kidney and urine relative to 125 I-hepcidin complexed to α 2 -macroglobulin) ( 8 ).…”
Section: Physiology Of Hepcidinmentioning
confidence: 99%
“…Up to 90% of circulating hepcidin is bound to α 2 -macroglobulin, and this complex was shown to reduce iron concentrations to a significantly greater extent than free hepcidin. It is argued that the reason is slower hepcidin urine excretion, but this remains to be confirmed in humans ( 8 ). In renal transplant recipients this could be of great significance, since their renal excretion is limited by graft function.…”
Section: Final Considerationsmentioning
confidence: 99%